2011
DOI: 10.1128/iai.01031-10
|View full text |Cite
|
Sign up to set email alerts
|

Genotype Is Correlated with but Does Not Predict Virulence of Vibrio vulnificus Biotype 1 in Subcutaneously Inoculated, Iron Dextran-Treated Mice

Abstract: Vibrio vulnificus is the leading cause of reported deaths from infections related to consumption of seafood in the United States. Affected predisposed individuals frequently die rapidly from sepsis. Otherwise healthy people can experience severe wound infection, which can lead to sepsis and death. A question is why, with so many people consuming contaminated raw oysters, the incidence of severe V. vulnificus disease is low. Molecular typing systems have shown associations of V. vulnificus genotypes and the env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
60
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 59 publications
6
60
2
Order By: Relevance
“…All cluster II strains possessed pilF type C, which has previously been correlated with pathogenicity (1,28) and was only rarely found in cluster I BT1 strains. In contrast to the study of Roig et al (28), in which nearly all clinical isolates possessed the pilF type C allele, more than half of the clinical strains in our strain collection possessed pilF type E. Altogether, our data on the distribution of type C and E alleles of the pilF, 16S rRNA, and vcg genes among environmental and clinical isolates from the Baltic Sea region support the opinion of Thiaville et al that E-type strains can be pathogenic and should not be classified as avirulent per se (31).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…All cluster II strains possessed pilF type C, which has previously been correlated with pathogenicity (1,28) and was only rarely found in cluster I BT1 strains. In contrast to the study of Roig et al (28), in which nearly all clinical isolates possessed the pilF type C allele, more than half of the clinical strains in our strain collection possessed pilF type E. Altogether, our data on the distribution of type C and E alleles of the pilF, 16S rRNA, and vcg genes among environmental and clinical isolates from the Baltic Sea region support the opinion of Thiaville et al that E-type strains can be pathogenic and should not be classified as avirulent per se (31).…”
Section: Discussionsupporting
confidence: 75%
“…Other key genes that may differentiate between the genomes of clinical and environmental genotypes were recently identified using a comparative genome analysis approach (29), and Kim et al identified further potential virulence factors by comparative transcriptomic analyses between clinical and environmental isolates using a cDNA microarray (30). Thiaville et al analyzed the virulence properties of 33 clinical and 36 environmental isolates of V. vulnificus biotype 1 from the United States in a mouse model and found that higher virulence was correlated with, but not exclusive to, the clinical genotype (31). While several studies examined the distribution and characteristics of this species from tropical regions and the United States, studies on pathogenic and nonpathogenic V. vulnificus strains from northern temperate waters are scarce.…”
mentioning
confidence: 99%
“…Of V. vulnificus strains isolated from clinical cases, 90% have the vcgC allele (C-genotype), while 87% of environmental isolates have the vcgE (E-genotype) allele (4,7). Although genotype correlates with virulence, it is not necessarily predictive, as shown by Thiaville et al They found that 3 of the 9 most virulent strains, when inoculated subcutaneously in iron dextran-treated mice, possessed the vcgE allele, which confirms that not only those strains with the vcgC allele are capable of causing disease (8).…”
mentioning
confidence: 76%
“…Despite these studies, no single, causal virulence factor has been found to be exclusively associated with clinical genotype strains (17). While the C/E genotyping scheme strongly correlates with virulence potential, this method does not strictly predict virulence (17).…”
mentioning
confidence: 99%
“…While the C/E genotyping scheme strongly correlates with virulence potential, this method does not strictly predict virulence (17). For example, some strains with the vcgE allele have been isolated from clinical cases, often from wound infections.…”
mentioning
confidence: 99%